PENGARUH SUBSTITUSI TEPUNG SORGUM FERMENTASI TERHADAP KARAKTERISTIK FISIK, KIMIA DAN ORGANOLEPTIK KUKIS - Seveline Seveline; Indah Putri Divia; Moh Taufik (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
The aim of this research is to find out the physical, chemical and organoleptic characteristics of cookies substituted by fermented sorghum flour and to determine the characteristics of the best cookies so that they can be used as alternative products based on local cereals. The study consisted of two stages, namely the manufacture of cookies and analysis. This study uses a completely randomized design with a combination of 50:50 flour and sorghum fermented flour and 100% wheat flour as a control. Data were analyzed using one-way analysis of variants (ANOVA) at 95% level and Duncan's continued test. The results showed that the used of fermentated sorghum flour as a substitute for flour making cookies had a significant effect on color, texture (level of hardness), moisture content and the level of panelist preference on cookie texture, but had no significant effect on protein content and the level of panelist freference on color, aroma, taste, aftertaste and overall of cookies produced.